Kajian Makro Ekonomi Sumatera Barat Tahun 2000 - 2010 - Adry, Melti Roza; Aimon, Hasdi; Anis, Ali (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT The purpose of this research are to know and analysis: 1. Influence of lagged consumption, disposable income dan lagged disposable income to consumption in West Sumatera.Â 2.Â Influence of lagged investment, economic, and lagged economic, interest rate dan lagged interest rate to investment in West Sumatera. 3.Influence of lagged interest rate, economics and legged, money supply and lagged money supply to interest rate in West Sumatera. 4. Influence of economics to tax in west sumatera. 5.Â Influence of economics to impor in West Sumatera. 6.Influensce of consumption, investment, government expenditure, export and impor to economic in West Sumatera. The Result of this research are (1). As partial lagged consumption, disposable income dan lagged disposable income have signifikan effect to consumption in West Sumatera (2) As partial lagged investment, economic, and lagged economic, has significant effect to investment in West Sumatera, but interest rate dan lagged interest rate has not significant effect. But as simlutaneos all variable has significant effect. (3).As partial lagged interest rate has significant effect to interest rate in West Sumatera. But economics and legged, money supply and lagged money supply has not signifikan influence to interest rate in West Sumatera 4.Economic has influence effect to tax in West Sumatera. 5. Economic has influence effect to import in West Sumatera. (6) As partial consumption, government expenditure, export and impor has significant influence to economic in West Sumatera, but investment has not significant effect to economics. Keywords: Economics, Consumsptions, Investment, Government Expenditure, Export, Import, Interest Rate, Tax